REARRANGEMENT OF CARBON AND NITROGEN FORMS IN PEAT AFTER PROGRESSIVE THERMAL OXIDATION AS DETERMINED BY SOLID-STATE 13C- AND 15N-NMR SPECTROSCOPY - Almendros G.; Knicker H.; Gonzalez-Vila F.J. (My University, 2003)
Peat samples subjected to thermal oxidation were studied by solid-state 13C- and 15N-NMR spectroscopy, so as to gain information on the thermal alteration of organic matter during processes such as natural fires or prescribed fires affecting soils. The 13C-NMR spectra show that heating (up to 180 s at 350#°C) increases the aromaticity of the original peat to values typical for black-carbon material, but these charred residues (at least after weight losses of ca. 25%) still contained heat-resistant alkyl carbon. The 15N-NMR spectrum of the original peat is dominated by a signal at -258 ppm, suggesting peptide-like material. In the heated samples a resonance line appearing at lower field indicates progressive formation of pyrrole- and indole-type compounds. Calculations based on weight loss, elemental composition and relative intensity distribution of the 13C- and 15N-NMR spectra demonstrate that the increasing concentrations of aromatic C-types and heterocyclic N-forms with progressive heating are not only caused by a relative enrichment concomitant with the selective thermal degradation of labile structures (mainly O-alkyl and amides) but correspond to newly-synthesised structures that were formed from aliphatic material.